PANDANGAN MASYARAKAT PINGGIRAN HUTAN TERHADAP PROGRAM PENGEMBANGAN AGROFORESTRI - Dewa Oka Suparwata (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2018)
Nowadays, development of agroforestry has been focused on the people living near forest. Positive views from community may have a good impact on agroforestry development program. This research aims to study the views of the forest outskrit community on the agroforestry development program in Dulamayo Barat village, Telaga Sub District, Gorontalo Regency, Gorontalo Province. The study used survey approach and focus group discussion (FGD) method. Respondents were all the members of agroforestry farmer group. The entire population were taken for interview (10 respondents) while FGD was attended by 26 participants. Data were analyzed descriptively. The result showed that 100% of the respondents want the program to be sustainable, although from the socio economic point of view the impact has not contributed significantly. From the respondents views of its benefit, 50% believe that the program is for critical land rehabilitation, 30% have a view for the improvement of environmental service, 10% view to increase community economy, and 10% view that the program is to eliminate erosion. These indicate that the community is concerned with agroforestry development, therefore, continuous facilitation is needed. Furthermore, the community expects to be actively involved in the agroforestry development program.